Primary and secondary hemophagocytic lymphohistiocytosis have different patterns of T‐cell activation, differentiation and repertoire. Issue 2 (3rd January 2017) - Ammann, Sandra; Lehmberg, Kai; zur Stadt, Udo; Janka, Gritta; Rensing‐Ehl, Anne; Klemann, Christian; Heeg, Maximilian; Bode, Sebastian; Fuchs, Ilka; Ehl, Stephan
Abstract : The illustrated phenotype is characteristic for patients presenting with different subtypes of HLH in the first year of life and demonstrates the pathophysiological principle. In older patients, most markers of T cell differentiation (apart from HLA‐DR) are very heterogenous also in healthy individuals, such that these phenotypic markers are of limited diagnostic value in patients beyond infancy. Abstract : Hemophagocytic lymphohistiocytosis (HLH) is a life‐threatening inflammatory syndrome characterized by hyperactivation of lymphocytes and histiocytes. T cells play a key role in HLH pathogenesis, but their differentiation pattern is not well characterized in patients with active HLH. We compared T‐cell activation patterns between patients with familial HLH (1°HLH), 2°HLH without apparent infectious trigger (2°HLH) and 2°HLH induced by a viral infection (2°V‐HLH). Polyclonal CD8 + T cells are highly activated in 1°HLH and 2°V‐HLH, but less in 2°HLH as assessed by HLA‐DR expression and marker combination with CD45RA, CCR7, CD127, PD‐1 and CD57. Absence of increased HLA‐DR expression on T cells excluded active 1° HLH with high sensitivity and specificity. A high proportion of polyclonal CD127 − CD4 + T cells expressing HLA‐DR, CD57, and perforin is a signature of infants with 1°HLH, much less prominent in virus‐associated 2°HLH. The similar pattern and extent of CD8 + T‐cell activation compared to 2° V‐HLH is compatible with a viral trigger of 1°HLH. However, in most 1°HLH patients no triggering infection was documented and the unique activation of cytotoxic CD4 + T cells indicates that the overall T‐cell response in 1°HLH is different. This may reflect different pathways of pathogenesis of these two HLH variants.